AN ERROR ANALYSIS IN USING SIMPLE PAST TENSE IN INCIDENT REPORT E-MAILS BY KIDS CLUB SOFITEL STAFF - Yoga Widiadnya, I Gusti Ngurah Bagus (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dwijendra, 2020)
Abstract This research aimed to find out the common errors of word order especially in using verb, to be, and noun phrase in writing incident report emails made by Kids club Sofitel staffs. The problem statement of this research was ?what are the types and the sources of error on the use of simple past tense in Kids club incident reports by email writing?. The objective of this research was to find out the types and the sources of errors that often occurred in the use of simple past tense in incident reports made by Kids club Sofitel staffs. To analyze the data, the researcher used descriptive qualitative method and used error analysis procedure to make clear explanation. The error collected was classified based on Dulay Strategy Taxonomy. The participants of this study consist of five staffs from Kids club Sofitel Bali Nusa Dua. By this analysis, the researcher found errors as follows: there were 132 errors were found in the staff?s incident reports. The total errors of Omission were 64 errors, Addition were 5 errors and Mis-formation were 63 errors and also 109 errors of Intralingual transfer and 23 errors of Interlingual transfer. So could be concluded that the most of error found was Omission and lowest of error found was Addition and the most of sources of error was Intralingual transfer. Keywords: Error Analysis, Simple Past Tense, E-mail.   Abstrak Abstrak. Penelitian ini bertujuan untuk mengetahui kesalahan umum urutan kata terutama dalam menggunakan kata kerja, menjadi, dan frasa kata benda dalam menulis email laporan kejadian yang dibuat oleh staf Kids club Sofitel. Pernyataan masalah dari penelitian ini adalah